ANALISIS NILAI TAMBAH PELAKU RANTAI PASOK ORGANISASI JARINGAN MADU HUTAN SUMBAWA (JMHS) MENGGUNAKAN METODE HAYAMI - Qashiratuttarafi Qashiratuttarafi; Andriyono Kilat Adhi; Wahyu Budi Priatna (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2018)
This study was aimed to analyze the added value in the supply chain of forest honey at Jaringan Madu Hutan Sumbawa (JMHS) organization. The respondents in this study are 30 honey hunter, 2 group leader, 2 JMHS cooperative and 1 marketing outlet Rumah Madu. Quantative descriptive analysis method was used to analyze the added value by using Hayami’s method (1987). The results from this study were the added value of forest honey from Madu Hutan Lestari cooperation is 0.5 persen highest than other chain actors. While the value added distribution of marketing outlets Rumah Madu has been the highest percentage of added value compared to other chain actors.